2014
DOI: 10.3844/ojbsci.2014.12.20
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Attenuates Hepatic and Cardiac Damage and Apoptosis in Rabbits Fed a High-Fat Diet

Abstract: A hypercholesterolemia diet has been associated with the hepatic and cardiac abnormalities and the pathological changes. The present work was designed to investigate the histological and immunohistochemical changes in the liver and heart of rabbits when fed high fat diet and the possible protective role of an antioxidant "taurine". Twenty-four male white New Zealand rabbits were divided into four groups, 6 rabbits each. Group 1, served as a control, rabbits fed with a normal diet. Group 2, (taurine group), rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…A clear hepatocyte radically arranged as cords or sheaths around central veins inside the portal lobule sinusoids were very clear between the cords of hepatocytes composed of endothelial and kupffer cells (figure 2a and b) in the present histological analysis of hepatic tissue in the normal group fed with a normal diet. The histological light microscopic analysis in the atherogenic group (rats fed a high-fat diet for 28 days) which shows certain changes in the liver structure, including congestion of the blood vessels and deposition of fat in the connective tissue between the lobules (figure 3 a and b), This observation was consistent with many studies that indicated that atherogenic diet induced fatty liver and hepatotoxicity [35,36] that suggested that hepatic tissue modifications were induced by a high cholesterol diet. In addition, other studies [37] indicate that atherogenic diets in rats with obesity have developed fatty liver disease.…”
Section: Liversupporting
confidence: 87%
“…A clear hepatocyte radically arranged as cords or sheaths around central veins inside the portal lobule sinusoids were very clear between the cords of hepatocytes composed of endothelial and kupffer cells (figure 2a and b) in the present histological analysis of hepatic tissue in the normal group fed with a normal diet. The histological light microscopic analysis in the atherogenic group (rats fed a high-fat diet for 28 days) which shows certain changes in the liver structure, including congestion of the blood vessels and deposition of fat in the connective tissue between the lobules (figure 3 a and b), This observation was consistent with many studies that indicated that atherogenic diet induced fatty liver and hepatotoxicity [35,36] that suggested that hepatic tissue modifications were induced by a high cholesterol diet. In addition, other studies [37] indicate that atherogenic diets in rats with obesity have developed fatty liver disease.…”
Section: Liversupporting
confidence: 87%
“…If left untreated, this can lead to liver necrosis and cirrhosis. In this study, the liver was also analyzed since it is the first organ to metabolize ingested cholesterol and is therefore the main target of the lipoxidative damage caused by an imbalance between generated free radicals and an ineffective antioxidant defense mechanism 71 .…”
Section: Discussionmentioning
confidence: 99%